2010
DOI: 10.1002/xrs.1261
|View full text |Cite
|
Sign up to set email alerts
|

Direct chromium speciation using X‐ray spectrometry and chemometrics

Abstract: Chromium is a chemical element that occurs in two principal distinct forms: trivalent (Cr(III)) and hexavalent (Cr(VI)). As chromium toxicity depends on its oxidation state, the concentrations of both the species should necessarily be determined, and not only that of total chromium. Using X‐ray spectrometry allied to chemometrics, this work presents a new method for chromium speciation, with no prior separation and/or preconcentration of Cr(III) and Cr(VI) species. Spectra of several solutions containing diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…In this study, a multivariate analysis named principal components analysis (PCA) was applied to examine and visualize any relevant and interpretable structure in the data, using statistical software PAST 3 program . PCA model is a powerful method for spectroscopic analysis like FTIR and XRD, and it was used as an exploratory tool, which permits to point out the differentiation and similarities among samples and allows seeing the effect of accelerated aging on the chemical and physical properties of NC‐based formulations. Usually, In PCA models, each cluster contains samples that have similar spectra and hence have similar properties; the farther the distance between clusters, the more different they are …”
Section: Methodsmentioning
confidence: 99%
“…In this study, a multivariate analysis named principal components analysis (PCA) was applied to examine and visualize any relevant and interpretable structure in the data, using statistical software PAST 3 program . PCA model is a powerful method for spectroscopic analysis like FTIR and XRD, and it was used as an exploratory tool, which permits to point out the differentiation and similarities among samples and allows seeing the effect of accelerated aging on the chemical and physical properties of NC‐based formulations. Usually, In PCA models, each cluster contains samples that have similar spectra and hence have similar properties; the farther the distance between clusters, the more different they are …”
Section: Methodsmentioning
confidence: 99%
“…Some forms of preliminary separation and pre-concentration like liquid-liquid extraction [17,18], cloud point extraction [19], ion-exchange [20,21] and solid phase extraction [22][23][24] are required. Bueno et al [25] reported direct chromium speciation using X-ray spectrometry allied to chemometrics without separation / preconcentration of Cr species with a detection limits of 17 and 50 g L −1 for Cr(III) and Cr(VI) respectively. X-ray fluorescence spectrometric determination of Cr(VI) after aliquat 336-AC assisted solid phase extraction was carried out by De Vito et al [26] which required no elution process.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most useful and well‐established chemometric tools is principal component analysis (PCA). PCA is the principal base of modern methods of treating multivariate data . PCA summarizes the information of the initial data set into a new set, which is smaller than the former.…”
Section: Introductionmentioning
confidence: 99%